Assessing Expected Long-term Benefits for the Olympic Games: Delphi-AHP Approach from Korean Olympic Experts. (December 2022) - Han, Seung-Jin; Lee, Won-Jae; Kim, So-Hee; Yoon, Sang-Hoon; Pyun, Hyunwoong
The Olympic legacy framework was proposed by the International Olympic Committee; however, it has not yet been discussed much in academia. This study identified a set of key dimensions and items out of 7 dimensions and 39 items from the Olympic legacy framework, along with the weight of each dimension and item. Based on the judgments of 12 Korean Olympic experts collected via the Delphi-analytical hierarchal process method, the results indicate that social development through sport is the most significant dimension, followed by economic value and brand equity, and urban development. The results also reveal that the most crucial of the 39 items are health and well-being benefits from the practice of recreational sport and physical activity from the social development through sport dimension, while the intangible cultural heritage of Olympism from the culture and creative development dimension was considered the least important. The results provide useful insight for evaluating the Olympic legacy framework for host or candidate cities and countries, as well as the International Olympic Committee.